Gender-Neutral Outcomes in IoT-Based Physics Education: A Non-Parametric Analysis of Hands-On IoT Tasks and Cognitive Achievement - Yudi Guntara; Siti Rosyadah Nurlia (CATHA SAINTIFICA, 2025)
This study aims to test the difference in practicum performance and cognitive ability between male and female students in making an IoT-based physics learning media project in the Physics Learning Media course. The research method used was descriptive-quantitative with a sample of 43 students (37 females, 6 males) of the class of 2022 at the Department of Physics Education, Sultan Ageng Tirtayasa University. The data collection instrument used a Hands-on Task (4 IoT practicum tasks) and a cognitive test in the form of an essay. Then the data were analyzed descriptively and inferentially (Mann-Whitney U Test). The results showed that there was no significant difference between genders in all practicum assignments (p = 0.320–0.981) or cognitive tests (p = 0.724). The average male scores were slightly higher on tasks 3–4 (83.33–89.17) and cognitive tests (3.68), but not statistically significant. These findings prove that IoT-based learning has the potential to create equality of technical and conceptual competencies, regardless of gender. Implicitly, the experiential learning approach with IoT projects needs to be optimized to encourage the active participation of all genders in STEM. The limitations of the study include sample imbalances and the scope of assessment that is not yet holistic